Efektivitas Perubahan Jam Sekolah terhadap Tingkat Kedisiplinan Siswa - Zahra, Muthia Ivana; Hutagalung, Febrianti; Rusnita, Ayu Novidaniati; Saragih, Theresia Julietta Rohdearni; Parhusip, Feby Adelia; Tarigan, Putri Juliani Br; Jamaludin, Jamaludin (Jurnal Pusat Studi Pendidikan Rakyat, 2023)
Discipline in learning is very important, because the attitude of discipline aims to be able to guard against deviant behavior and things that can interfere with the learning process. Discipline makes students trained and have the habit of doing good actions and can control their every action so that students will obey, comply and be orderly towards teaching and learning activities. In learning, discipline is needed because without awareness of carrying out the previously set rules, learning will not run effectively and optimally. The research method used in this study uses the type or research approach of Library Studies (Library Research). What is meant by literature study is all efforts made by researchers to collect information that is relevant to the topic or problem to be or is being researched. Education is one of the most important factors and the state takes this into account. Therefore, each country also has a system or regulation prepared to regulate how education is organized in that country, as well as the desired educational model, the curriculum to be taught, and the duration of learning. Discipline is a condition that is formed from a process and behavior that shows the value of obedience, obedience and order. Discipline in schools is expected to create a comfortable and peaceful learning atmosphere in the classroom. Disciplined students are students who tend to be punctual, follow all school rules and behave according to predetermined standards.